Biosaline Agriculture as a Climate Change Adaptation for Food Security - Choukr-Allah, Redouane; Ragab, Ragab (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents recent research work on Biosaline Agriculture presented during First International Forum on Biosaline Agriculture in Laayoune, Morocco from May 3rd to May 4th 2019. The aim of this book is to showcase the global potential of Biosaline agriculture, provide an update on the development of recent innovations in the field of Biosaline agriculture, the best management practices to safely use brackish and saline water, highlight the use of non-conventional water in marginal environment production and the current advanced technologies of desalination of brackish and seawater. The different chapters will also discuss solutions that are adapted to local conditions as part of a sustainable development perspective. The book provides up-to-date technical and scientific data on growing crops under marginal environment so as to encourage the dissemination of this knowledge in the best practices to increase the productivity in Biosaline agriculture, in view of the potential to contribute to food security. The book is expected to stimulate interest in the non-conventional water resources and crops among junior and senior researchers and among those who are increasingly focused on exploiting marginal environments. It will also be of interest to decision-makers and the public and private sectors to jointly address the issues of food security especially of the poor and vulnerable people living in marginal environments worldwide by providing innovative technology transfer.
Chapter 1. Introduction to the book -- Chapter 2. Best practices for saline and brackish water management -- Chapter 2.1 Salt-affected soils and their management in the Middle East and North Africa (MENA) region: A holistic approach -- Chapter 2.2 Innovation and practical experience of using saline water at farm level in Tunisia -- Chapter 2.3 Soil and nutrient management under saline conditions -- Chapter 2.4 Irrigation management under saline conditions in MENA and Sub-Saharian conditions: Lessons learned -- Chapter 2.5 Irrigation Water Management under Salinity Conditions in Arid Regions -- Chapter 2.6 Seed priming and Nano priming techniques as tools to alleviate osmotic stress in legumes -- Chapter 3. Using saline water for conventional, nonconventional and forage crops -- Chapter 3.1 Exploration and collection of quinoa's wild ancestor in Argentina -- Chapter 3.2 Multilocality evaluation of alternative forage crops grown under salinity conditions in the south of Morocco -- Chapter 3.3 Innovation and Practical Experience of Using Saline Water at the Farm Level in Tunisia -- Chapter 4. Land management when irrigating with saline water -- Chapter 4.1 Do cultivating methods improve crop yield under saline condition in semi-arid areas? -- Chapter 4.2 Posphoypsum as potential amendment and fertilizer for crop nutrition and salt affected soils remediation -- Chapter 5. The challenges faced when using of non-Conventional water in agriculture -- Chapter 5.1 Status, Drivers and Suggested Management Scenarios of salt affected soils in Africa -- Chapter 5.2 The use of nonconventional water resources in agriculture in the Gulf Cooperation Council Countries: Key challenges and opportunities for the use of treated wastewater -- Chapter 6. Use of models as management tools -- Chapter 6.1 SALTMED model as a tool for water, crop, field and N-fertilizers management -- Chapter 7. Use of desalination technology to produce non-saline water for irrigation -- Chapter 7.1 Is desalination for agriculture sustainable? -- Chapter 7.2 The Technological Challenges of Desalination for Irrigation in Morocco.
Keywords: Agriculture; Water; Hydrology; Climatology; Plant physiology; Biodiversity; Agriculture; Water; Climate Sciences; Plant Physiology; Biodiversity